PENGARUH WORD OF MOUTH DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA RESTORAN RUNNING KOREAN STREET FOOD DI MALL PLAZA MULIA SAMARINDA - Nurul Qomariah (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
The purpose of this research is to know the variables consisting of Word of Mouth and Brand Image are simultaneously, partially, and dominant against purchasing decisions on Running Korean Street Food in Samarinda. The study uses Word of Mouth theory with five indicators, namely Talkers, Topics, Tools, Taking Part, and Tracking. Then the Brand Image theory with three indicators, namely corporate image, product image, user image. Purchasing decision theory, namely with five indicators of introduction of needs, information retrieval, alternative evaluation, purchasing decisions, post-purchase behavior. Using quantitative descriptive research method is research using survey through questionnaire. The population in this study was the consumer who came to Running Korean Street Food in Samarinda. Sampling techniques using non-probability sampling technique is Simple Random Sampling with a sample number of 100 respondents. This research is a quantitative study. The analytical techniques used are multiple linear regression analyses with SPSS version 25 applications. The results of this study show that from the results of the F test tally it can be stated that Word of Mouth and Brand Image are of significant effect simultaneously or simultaneous to purchasing decisions. From the results of test counting T can be stated that between Word of Mouth and Brand Image. Brand Image is a partially significant variable of influence on purchasing decisions on Running Korean Street Food in Samarinda. 3). From the dominant test result is known that the variable Brand Image is a variable that is dominant influence on the purchase decision on Running Korean Street Food with a value of counting T 4,889 and the value of Sig. 0.000 or smaller than 0.05.